2012
DOI: 10.1089/gtmb.2011.0322
|View full text |Cite
|
Sign up to set email alerts
|

Association of Androgen Receptor, Prostate-Specific Antigen, andCYP19Gene Polymorphisms with Prostate Carcinoma and Benign Prostatic Hyperplasia in a North Indian Population

Abstract: The genes involved in androgen pathway and metabolism have been reported to contribute considerably to prostate carcinoma (CaP) risk. The present study investigated the association of androgen receptor (AR), prostate-specific antigen (PSA or KLK3), and cytochrome P450 (CYP19) gene polymorphisms in CaP (n=105) and benign prostatic hyperplasia (BPH) (n=120) in comparison to normal healthy controls (n=106) in an Indian population. We also evaluated the functional consequences of these gene variants on AR and PSA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Among the rest of 22 studies, 15 more were removed due to letter ( n = 1), review ( n = 1) and without controls ( n = 13). Therefore, a total of 7 independent studies [1521] were ultimately included in this meta-analysis, containing 758 cases and 752 controls. The principal characteristics of included studies are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the rest of 22 studies, 15 more were removed due to letter ( n = 1), review ( n = 1) and without controls ( n = 13). Therefore, a total of 7 independent studies [1521] were ultimately included in this meta-analysis, containing 758 cases and 752 controls. The principal characteristics of included studies are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In a Turkey population, Gunes et al found an increasing effect of the GG genotype of PSA -158G/A polymorphism on BPH susceptibility, with an age-adjusted OR of 2.77 (95% CI = 1.277-6.012) [20]. On the contrary, Abha Soni et al insisted that the genotypes AA and GA of this polymorphism were significantly related to elevated risk of BPH in their study involving 120 BPH cases and 105 controls in Indians [21]. Whereas, a study by Alptekin and colleagues detected no statistically significant difference in the frequencies of genotypes or alleles of PSA -158G/A polymorphism between controls and BPH cases in Turks, suggesting that the polymorphism might not have independent influence on the disease onset [18].…”
Section: Disscussionmentioning
confidence: 99%
“…Many studies showed that increased risk of symptomatic BPH and LUTS when deletions of Glutathone S-transferase enzyme genes 18 . Another study demonstrated that 16-fold risk of BPH in the presence of the prostate specific antigen (PSA) G-158A single nucleotide polymorphism 19 .…”
Section: Risk Factorsmentioning
confidence: 99%
“…[39] Another North Indian study demonstrated a 2-fold risk of histologic BPH in men with CAG repeats in the androgen receptor gene and a 16-fold risk in the presence of the prostate specific antigen (PSA) G-158A single nucleotide polymorphism. [40]…”
Section: Risk Factors For Bph and Lutsmentioning
confidence: 99%